The Victorian Girl and the Feminine Ideal. - Gorham, Deborah (Routledge library editions. Women's history., 2012)
In Victorian England, the perception of girlhood arose not in isolation, but as one manifestation of the prevailing conception of femininity. Examining the assumptions that underlay the education and upbringing of middle-class girls, this book is also a study of the learning of gender roles in theory and reality. It was originally published in 1982. The first two sections examine the image of women in the Victorian family, and the advice offered in printed sources on the rearing of daughters during the Victorian period. To illustrate the effect and evolution of feminine ideals over th.